Green Chemistry Metrics A Guide to Determining and Evaluating Process Greenness - Dicks, Andrew (Springer, 2015)
This contribution to SpringerBriefs in Green Chemistry outlines and discusses the four major green chemistry metrics (atom economy, reaction mass efficiency, E factor and process mass intensity), at a level that is comprehensible by upper-level undergraduates. Such students have previously received fundamental training in organic chemistry basics, and are ideally positioned to learn about green chemistry principles, of which metrics is one foundational pillar. Following this, other green metrics in common use are discussed, along with applications that allow important calculations to be easily undertaken. Finally, an introduction to metrics in the context of life cycle analyses is presented. It should be noted that no other available publication teaches green chemistry metrics in detail with an emphasis on educating undergraduates, whilst simultaneously providing a contemporary industrial flavour to the material.